Understanding, Investigating, and promoting deep learning in language education: A survey on chinese college students' deep learning in the online EFL teaching context - Jiang, Ruihong (Frontiers in Psychology, 2022)
This study aims to better understand deep learning in language education by establishing the four-dimension theoretical construct of deep learning firmly grounded in empirical data and theoretical evidence. The study additionally attempts to investigate and promote deep learning by conducting a survey involving 533 college students in the online EFL teaching context in China. Concretely, this study initially synthesized theoretical insights from deep learning in the education domain and related theories in Second Language Acquisition (SLA) and thus proposed the four-dimension theoretical construct of deep learning involving the motivation of deep learning, the engagement of deep learning, the strategy of deep learning, and the directional competence of deep learning. This study subsequently undertook a questionnaire survey utilizing a standardized instrument to confirm hypothesized theoretical construct and further investigate the current status and salient differences in students’ deep learning in online EFL teaching. Exploratory factor analysis (EFA), Confirmation factor analysis (CFA), and Pearson’s correlation test verified a positively correlated four-dimension theoretical construct of deep learning with high composite reliability and good convergent validity. Moreover, the main results in descriptive analysis, ANOVA, etc., revealed that the level of students’ deep learning marginally reached the median, with the lowest mean of directional competence and the highest mean of motivation; students manifested more instructional motives, neglect of deploying skilled-based cognitive strategies, and deficiency of language application skills, etc.; there existed some significant differences of deep learning and four sub-dimensions across the grade, English proficiency, EFL course, vision groups. Eventually, this study proffered possible explanations and five appropriate strategies to scaffold and promote students' deep learning in online EFL teaching. Hopefully, this study will be a pioneering effort to clear away the theoretical muddle of deep learning construct in language education and be illuminating to further improve effectiveness in the online EFL teaching context.